The Kiev Folia: An interdisciplinary approach to unravelling the past of an ancient Slavonic manuscript. (February 2022) - Cappa, Federica; Piñar, Guadalupe; Brenner, Simon; Frühmann, Bernadette; Wetter, Wilfried; Schreiner, Manfred; Engel, Patricia; Miklas, Heinz; Sterflinger, Katja
Abstract: This interdisciplinary research on the Kiev folia, a 10th century Slavonic manuscript, shows how material and biological analyses as well as imaging methods can be applied to answer relevant questions that contribute to a better understanding of the history and conservation of ancient manuscripts. By applying non-invasive analytical methods, including X-ray Fluorescence analysis (XRF) and Fourier Transform Infrared spectroscopy in reflection mode (rFTIR), calcium oxalate related to the degradation phenomena of the ink material was detected, showing rFTIR bands at 1644 cm −1 and 1327 cm −1 . Moreover, potassium ferrocyanide was identified on the peculiar blue stains visible on some folios. Multispectral images of these stains improved the legibility of the underlying letters in the near infrared range. Finally, shotgun metagenomic analyses gave insight into the possible animal origin of the skin(s) used for the manufacture of the codex and the microbiome colonizing its surface. The microbiome consisted mainly of viruses (53%) and bacteria (47%) represented by halotolerant/halophilic bacteria as well as bacteria and viruses typical of the human microbiome. In contrast, the proportion of eukaryotes (0.05%) and archaea (0.07%) was very low. This information served to determine the conservation status and the risk of deterioration of the manuscript. Highlights: This interdisciplinary approach answers scientific questions related to ancient manuscripts. XRF and rFTIR show the application of minium, iron gall and carbon black inks. The composition of the peculiar blue stains was identified as potassium ferrocyanide. Shotgun metagenomic analysis gave insight into the possible animal origin of the skin. The microbiome showed halotolerant and commensal bacteria of the human microbiome.